WiFiMon App Measuring Wi-Fi Performance as Experienced by End - Users - Kurt Baumann; Christos Bouras; Vasileios Kokkinos; Nikolaos Papachristos; Kostas Stamos (24th International Conference on Telecommunication (ICT 2017), 2017)
The measurement of quality and efficiency of a wireless Wi-Fi network is particularly difficult, as there is not a single tool that can record measurements from all sides of the system, i.e. from both the access point and the end-user. Existing tools are able to monitor the overall quality of the wireless network; although they cannot determine how end-users experience the quality of Wi-Fi in a particular part of the network at a given time. In this paper we present a novel tool, named WiFiMon, which enables measuring, recording and exporting statistics regarding the quality of a Wi-Fi network as experienced by the end-users. The measurements are triggered by the end-users when they visit WiFiMon-enabled websites and/or run WiFiMon-enabled mobile applications and are recorded without users’ intervention. Main goal of WiFiMon is to give network administrators a better overview on how the endusers experience the conditions of the Wi-Fi network.